2019
DOI: 10.31878/ijcrpp.2019.32.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha, beta momorcharin fruit extract with the combination of paclitaxel in the treatment of glioma cancer in-vivo.

Abstract: The vegetable Momordica charantia L., (family: Cucurbitaceae) is a scientific name of the plant and its fruit. It is also known by other names, for instance in the USA it is known as Bitter gourd or balsam pear while its referred to as the African cucumber in many African countries.  M.charantiais believed to posse’s anti-carcinogenic properties and it can modulate its effect via xenobiotic metabolism and oxidative stress. This study was specifically designed to investigate the cellular mechanisms whereby α, β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several studies have reported that the water-soluble extract of M. charantia can exert anti-cancerous activity through inhibition of DNA, RNA and cellular protein synthesis [3][4][5][6][7]. The fruit juice of M. charantia has been found to increase glucose up take by several tissues in vitro and moreover, it can increase the storage of glycogen by the liver [8][9][10]. Cyclophosphamide (CP) is an alkylating agent and is usually administrated orally or intravenously and much less frequently intramuscularly or intraperitoneally [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the water-soluble extract of M. charantia can exert anti-cancerous activity through inhibition of DNA, RNA and cellular protein synthesis [3][4][5][6][7]. The fruit juice of M. charantia has been found to increase glucose up take by several tissues in vitro and moreover, it can increase the storage of glycogen by the liver [8][9][10]. Cyclophosphamide (CP) is an alkylating agent and is usually administrated orally or intravenously and much less frequently intramuscularly or intraperitoneally [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%